Multi-time Combined Gas and Electric System Optimal Power Flow Incorporating Wind Power. (November 2016) - Chen, Shuang; Sun, Guoqiang; Wei, Zhinong; Chen, Sheng; Li, Yichi
Abstract: To alleviate environment pollution, it has become a tendency for energy adjustment that natural gas is taking the place of fossil fuels. The coupling between natural gas system and electric system is being strengthened by gas-fired power plants. A multi-time combined gas and electric system optimal power flow (M-GEOPF) model is proposed aiming at minimizing the overall cost. To address available wind power uncertainty, underestimation and overestimation of wind power are considered in the model. A test case on the combined IEEE 39-bus system and Belgium 20-node natural gas system is performed to verify the effectiveness of the proposed method.